Impact of Weblog to Increase English Essay Writing Ability: English - Euis Meinawati; Sri Arfani (Prodi Tadris Bahasa Inggris, 2023)
Abstract The purpose of this research is to get the impact of weblogs on English essay writing skills. This study used a quasi-experimental study with a one-group pre-test and post-test experimental design. The sample in this study were students of the English Program at BSI University, Jakarta. 50 students participated in the research process. The treatment process was carried out in 14 meetings and before treatment students were given a pre-test and after treatment, students received a post-test. Data was collected using documentation taken from the results of students' English essay writing tests. The data analysis technique uses a two-sample paired t-test for the mean. The results of the study concluded that the results of the t-test showed t-Stat < t-table (-32.4678 < 2.0095), meaning that weblogs have a good level of effectiveness in improving the ability to write English essays. Students understand the steps for developing essay writing well. The results of this study have implications for understanding the concept of using multimedia technology for students to write English essays which can lead to easy access anywhere and anytime.